The Influence of Female Directors on Earnings Quality: Political Connections, Family Ownership, and Institutional Ownership as Moderating Variables - Lusiarni, Wisa; Suranta, Eddy (Dinasti Publisher, 2025)
This research aims to analyze the influence of female directors on earnings quality with political connections, family ownership and institutional ownership as moderating variables. This research is based on Agency Theory which emphasizes the role of female directors in reducing information asymmetry so that it can improve the earnings quality by reducing profit manipulation. This research was conducted using quantitative methods. The research sample is 84 manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period in accordance with the set criteria. The data was processed using SPSS Statistics 21. Information is obtained from annual reports through idx.co.id and CESGS. Samples were selected using the purposive sampling technique. The results of the study showed that female directors had no influence on the earnings quality. Political connections do not moderate the influence of female directors on the earnings quality, while family ownership and institutional ownership moderate the influence of female directors on the earnings quality. From the results of the study, it can be concluded that the greater the family ownership and institutional ownership in a company and its board of directors, most of which are women, are able to improve the earnings quality. This is because family ownership and institutional ownership are monitoring mechanisms to minimize profit manipulation.